Bioenergetic adaptation in response to autophagy regulators during rotenone exposure. (21st August 2014) - Giordano, Samantha; Dodson, Matthew; Ravi, Saranya; Redmann, Matthew; Ouyang, Xiaosen; Darley Usmar, Victor M.; Zhang, Jianhua
Abstract Parkinson's disease is the second most common neurodegenerative disorder with both mitochondrial dysfunction and insufficient autophagy playing a key role in its pathogenesis. Among the risk factors, exposure to the environmental neurotoxin rotenone increases the probability of developing Parkinson's disease. We previously reported that in differentiated SH‐SY5Y cells, rotenone‐induced cell death is directly related to inhibition of mitochondrial function. How rotenone at nM concentrations inhibits mitochondrial function, and whether it can engage the autophagy pathway necessary to remove damaged proteins and organelles, is unknown. We tested the hypothesis that autophagy plays a protective role against rotenone toxicity in primary neurons. We found that rotenone (10–100 nM) immediately inhibited cellular bioenergetics. Concentrations that decreased mitochondrial function at 2 h, caused cell death at 24 h with an LD50 of 10 nM. Overall, autophagic flux was decreased by 10 nM rotenone at both 2 and 24 h, but surprisingly mitophagy, or autophagy of the mitochondria, was increased at 24 h, suggesting that a mitochondrial‐specific lysosomal degradation pathway may be activated. Up‐regulation of autophagy by rapamycin protected against cell death while inhibition of autophagy by 3‐methyladenine exacerbated cell death. Interestingly, while 3‐methyladenine exacerbated the rotenone‐dependent effects on bioenergetics, rapamycin did not prevent rotenone‐induced mitochondrial dysfunction, but caused reprogramming of mitochondrial substrate usage associated with both complex I and complex II activities. Taken together, these data demonstrate that autophagy can play a protective role in primary neuron survival in response to rotenone; moreover, surviving neurons exhibit bioenergetic adaptations to this metabolic stressor. Exposure to the neurotoxin rotenone is a risk factor for Parkinson's disease. We tested the hypothesis that autophagy is protective against rotenone toxicity in primary neurons. Exposure to nanomolar concentrations of rotenone caused immediate mitochondrial dysfunction, associated with a suppression of macroautophagy. However, mitophagy occurred that was independent of LC3II accumulation, and the surviving neurons exhibited adaptations to their cellular bioenergetic profiles. Cotreatment with the autophagy enhancer rapamycin was protective, whereas further inhibition of autophagy with 3‐methyladenine (3‐MA) exacerbated cell death, resulting in additional bioenergetic adaptations in the surviving neurons. <boxed-text content-type="graphic" id="jnc12844-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>